Medical Informatics in Morocco: Casablanca Medical Informatics Laboratory - Othmani, M. Bennani; Diouny, S.; Balar, K. (Yearbook of Medical Informatics, 2007)
In 2005, Medical Informatics Laboratory (CMIL) became an independent research unit within the Faculty of Medicine and Pharmacy of Casablanca. CMIL is currently run by three persons (a university professor, a data processing specialist and a pedagogical assistant). The objectives of CMIL are to promote research and develop quality in the field of biomedical data processing and health, and integrate new technologies into medical education and biostatistics. It has four units: Telehealth Unit, Network Unit, Biostatistics Unit, Medical data processing Unit.The present article seeks to give a comprehensive account of Casablanca Medical informatics laboratory (CMIL) activities. For ease of exposition, the article consists of four sections: Section I discusses the background of CMIL; section II is devoted to educational activities; section III addresses professional activities; and section IV lists projects that CMIL is involved in.Since its creation, CMIL has been involved in a number of national and international projects, which have a bearing on Telemedicine applications, E-learning skills and data management in medical studies in Morocco.It is our belief that the skills and knowledge gained in the past few years would certainly enrich our research activities, and improve the situation of research in Medical informatics in Morocco.
Keywords: Medical informatics; Morocco; telemedicine; distance education; hospital information systems